Pemberdayaan Masyarakat dalam Produksi Kerupuk Udang Vaname di Desa Tanjung Keramat - Suriyani, Meta; Zulfiani, Zulfiani; Fatimah, Fatimah; Rusli, Rusli; Safrizal, Safrizal (Pencerah, 2023)
Tanjung Keramat Village, Banda Mulia District, Aceh Tamiang Regency is located on the coast, there is a fisheries group called Raseuki Tanjung which is a fish and shrimp cultivation group. The abundant results of pond fish and shrimp cultivation are sold raw directly to local markets. Innovation has not yet been carried out into processed food products for marketing. The partner group comes from fishermen's wives, who want to become new entrepreneurs. Community Service (PKM) Samudra University (UNSAM) carries out community empowerment starting from the areas of production, governance and business management as well as marketing (upstream and downstream of the business). This community service has supported partner groups in Tanjung Keramat Village to become new entrepreneurs. Starting with utilizing the potential raw material for vaname shrimp available in Tanjung Keramat Village, as the basic ingredient for shrimp crackers. The partner group has been able to produce vaname shrimp crackers and also understands management and marketing.